Financing Mechanisms for Small Scale Renewable Energy Projects in Malaysia - Indra Khairil, Bahrain (2011)
The purpose of this analytical research paper is to find some feasible measures regarding financial issue faced in Malaysia’s renewable energy project and globally, and to promote biomass technology to the industrial development of Malaysia’s small scale renewable energy projects. The paper summarizes the status and studies the problems of renewable energy development (financing gap), and then puts forward some proposals for the financing mechanism and potential of palm’s biomass in Malaysia’s small scale renewable energy project based on international report and local research. As this is only a analytical research paper and many of its suggestions require rigorous testing and previous secondary data. The authors would suggest that further research is needed to compare experience of local industry in financing mechanism and technology used in small scale renewable energy project.